2019
DOI: 10.1016/j.jctb.2018.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Minimum number of edges that occur in odd cycles

Abstract: If a graph G has n ≥ 4k vertices and more than n 2 /4 edges, then it contains a copy of C 2k+1 . In 1992, Erdős, Faudree and Rousseau showed even more, that the number of edges that occur in a triangle of such a G is at least 2 n/2 + 1, and this bound is tight. They also showed that the minimum number of edges in G that occur in a copy of C 2k+1 for k ≥ 2 suddenly starts being quadratic in n, and conjectured that for any k ≥ 2, the correct lower bound should be 2n 2 /9 − O(n). Very recently, Füredi and Maleki … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 35 publications
(44 reference statements)
0
11
0
Order By: Relevance
“…The second part of our Conjecture 1, namely that the extremal graph should be from a G(a, b, c), is still open. Grzesik, P. Hu, and Volec [7] using Razborov's flag algebra method showed that every nvertex graph with n 2 /4 + 1 edges has at least (n 2 /4) − n 2 /8(2 + √ 2) − εn 2 pentagonal edges for n > n 0 (ε) for every ε > 0. They also proved that those graphs have at most n 2 /36 + εn 2 C 2k+1 -edges for n > n k (ε) for every ε > 0 and k ≥ 3.…”
Section: Further Problems Minimizing C 2k+1 Edgesmentioning
confidence: 99%
“…The second part of our Conjecture 1, namely that the extremal graph should be from a G(a, b, c), is still open. Grzesik, P. Hu, and Volec [7] using Razborov's flag algebra method showed that every nvertex graph with n 2 /4 + 1 edges has at least (n 2 /4) − n 2 /8(2 + √ 2) − εn 2 pentagonal edges for n > n 0 (ε) for every ε > 0. They also proved that those graphs have at most n 2 /36 + εn 2 C 2k+1 -edges for n > n k (ε) for every ε > 0 and k ≥ 3.…”
Section: Further Problems Minimizing C 2k+1 Edgesmentioning
confidence: 99%
“…We believe that the method of Grzesik, Hu and Volec [6] should be sufficient to give the exact smallest number of C 2k+1 -edges in a graph with n vertices and e edges, for any fixed k 2, provided that n is sufficiently large. Furthermore, their stability result should be sufficient to establish that, for sufficiently large n, the construction described earlier is the unique extremal construction.…”
Section: Problem 72mentioning
confidence: 99%
“…Very recently, more progress on Problem 7.2 was made by Grzesik, Hu and Volec [6]. For any fixed k 2, they obtained asymptotically sharp bounds for the smallest possible number of C 2k+1 -edges in a graph with n vertices and at least n 2 /4 + 1 edges, using the method of flag algebras.…”
Section: Problem 72mentioning
confidence: 99%
“…A less studied but still quite natural question is to maximise the number of edges that do not belong to any forbidden subgraph. Such problems in the Turán context (where we are given the order n and the size m > ex(n, H) of a graph G) were studied in [13,19,22,23]. In the Ramsey context, a problem of this type seems to have been first posed by Erdős, Rousseau, and Schelp (see [12,Page 84]).…”
Section: Introductionmentioning
confidence: 99%